The association between alterations in redox homeostasis, cortisol, and commonly used objective and subjective markers of fatigue in american collegiate football - McKay, B. A.; Delaney, J. A.; Simpkin, A.; Larkin, T.; Murray, A.; Pedlar, C. R.; Lewis, N. A.; Sampson, J. A. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To assess associations between a free oxygen radical test (FORT), free oxygen radical defense test (FORD), oxidative stress index, urinary cortisol, countermovement jump (CMJ), and subjective wellness in American college football.